USING ERP SYSTEM TO TEACH ACCOUNTING COURSES - Bae, Benjamin; Lee, C. Christopher (International Journal of Accounting & Finance Review, 2021)
This paper discusses the use of Enterprise Resource Planning (ERP) systems as a teaching tool in Accounting Courses.  Students can understand better the accounting cycle and business transaction processing by doing exercises and projects using the ERP system because it clearly shows the complete transaction cycle from the beginning to the end in a systematic and integrated way.   Specifically, practical suggestions and usages in the class setting are illustrated based on the SAP system. This hands-on and active learning approach greatly enhances the learning of Accounting Courses such as financial and managerial accounting courses, finance courses, and information systems courses.JEL Classification Codes: G2, M1, M4.